The Evaluation of Hemodynamic and Endocrine Response and Nesfatin-1 in Patients Undergoing Inhalation and Total Intravenous Anesthesia - Aksu, Ahmet; Demırel, Ismail (My University, 2025)
Purpose: The aim of this study was to investigate the effects of different anesthesia techniques on the surgical stress response and nesfatin-1 levels. Materials and Methods: This prospective, randomized, controlled study was conducted between March and June 2015. Ninety patients undergoing septoplasty were randomized into three groups: Desflurane + N2O (Group 1), Desflurane + Remifentanil (Group 2), and Propofol + Remifentanil (Group 3). Blood samples were collected immediately before induction, at the 30th minute in the postoperative recovery room, and at the 24th postoperative hour. Serum insulin, glucose, adrenaline, noradrenaline, cortisol, and nesfatin-1 levels were measured. Results: There were no significant differences between groups in glucose, adrenaline, noradrenaline, and nesfatin-1 levels at any time point (p > 0.05). However, insulin levels at the 24th postoperative hour were significantly higher in Group 1 compared to Group 3 (18.24 miu/ml vs. 5.52 miu/ml; p < 0.05). Cortisol levels measured at the 30th postoperative minute in Group 3 showed a significant increase compared to the other groups (10.82 ?g/dl; p < 0.05). Conclusion: Different anesthesia techniques produced similar effects on hemodynamic and endocrine responses as well as nesfatin-1 levels in patients undergoing septoplasty.
Keywords: Inhalation anesthesia; Nesfatin-1; TIVA; surgical stress response